PEMAHAMAN KOMPETENSI ABAD 21 DALAM FILM FREEDOM WRITERS (2007) - Arbi, Anggun Purnomo; Prasetyo, Muhammad Andi Tanri; Akhlish, Muhammad (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2023)
This study aims to analyze the understanding of 21st century competencies reflected in the film